Reinterpreting Democracy and Pluralism: Nurcholish Madjid’s Intellectual Legacy and Its Relevance for Contemporary Indonesia - Ichwayudi, Budi; Purwanti, Nuril Atfiani; Saputra, Moh. Iqbal Firdaus; Syabrowi, Syabrowi (Jurnal Pemikiran Islam, 2025)
This article examines the contemporary relevance of Nurcholish Madjid’s thought on democracy and pluralism in Indonesia. Through a qualitative literature review guided by Miles and Huberman’s analytical framework, the study synthesizes Madjid’s intellectual formation, core democratic principles, and his nuanced approach to the relationship between Islam and the state. The findings highlight Madjid’s persistent insistence that democracy is not a finished project but an ongoing, adaptive process—one that demands ethical substance, critical participation, and continuous negotiation between religious values and civic institutions. By comparing Madjid’s ideas to those of prominent Muslim thinkers such as Yusuf al-Qaradawi, Abdullahi An-Na’im, Khaled Abou El Fadl, and Asef Bayat, the article situates his contribution within both Indonesian and broader Islamic discourses. Madjid’s advocacy for substantive democracy and active pluralism is shown to be deeply rooted in both his personal experience and his reading of Indonesia’s diverse society. The analysis demonstrates that, in the face of growing populism, the instrumentalization of religious identity, and persistent challenges to civil rights, Madjid’s vision remains urgently relevant. Rather than offering a static blueprint, Madjid’s legacy is framed as a provocation to rethink and revitalize democracy as an open, unfinished process. His call for loyal opposition, civil courage, and social learning is presented as both a challenge and a guide for Indonesia’s ongoing democratic experiment. The article concludes that Madjid’s ideas offer not easy answers, but a critical lens and a moral discipline for navigating the dilemmas of democracy, pluralism, and national identity in Indonesia today.